Are Firms in Corporate Groups More Resilient During an Economic Crisis? Evidence from the Manufacturing Sector in Poland - Barbara Jankowska; Katarzyna Mroczek-Dąbrowska; Marian Gorynia; Marlena Dzikowska (Journal of Entrepreneurship, Management and Innovation)

(untitled)
Corporate groups are specific types of business networks that generate particular advantages for firms. They allow corporates to reduce costs, develop the pool of resources and increase the flexibility of operations and responses to external shocks among others. The above mentioned benefits are of even greater importance during times of economic turbulence. Their involvement in a corporate group should theoretically allow firms to perform better. The aim of this study is to verify whether corporate group membership truly translated into a firm’s higher input competitiveness and a firm’s better performance during the recent economic crisis. First, we try to investigate if the input competitiveness is higher in the case of firms being members of corporate groups. Second, we test whether the involvement in a corporate group matters for the performance of the firms. Using critical in-depth literature studies and conducting the primary empirical research using the CATI (computer-assisted telephone interviewing) method we strive to verify the following hypothesis - the higher a company’s input competitiveness during the economic crisis, the better a competitive position the company achieves. The empirical research encompasses more than 700 corporates from the manufacturing sector in Poland during the global economic crisis and shortly afterwards. To investigate the issue we use the following methods of statistical analysis – cluster analysis, non-parametric tests and correlation coefficients. The results of the study show that firms involved in both Polish and international corporate groups were more resilient during the economic crisis than those which were not.